2021
DOI: 10.3390/ijerph18083959
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Hedonic and Eudaimonic Motives for Activities-Revised Scale in Chinese Adults

Abstract: The Hedonic and Eudaimonic Motives for Activities-Revised scale (HEMA-R) is one of the most extensively used instruments to assess how people pursue well-being. The main aims of the present research were to translate HEMA-R into Chinese and test its construct and predictive validity as well as measurement invariance across gender. In Study 1, we conducted confirmatory factor analysis with data containing 1090 Chinese undergraduates, and replicated the two-factor model which has been found in other studies. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Respondents reported the degree to which they used each motive when engaging in their daily activities, using a seven-point Likert scale ranging from 1 (not at all) to 7 (very much). The scale has been found to have good psychometric properties in Chinese samples [ 9 ]. In the present study, the two-factor model had an adequate fit index (χ 2 (29) = 84.52, χ 2 /df = 2.92, the comparative fit index (CFI) = 0.95, the Tucker-Lewis index (TLI) = 0.93, the root mean square error of approximation (RMSEA) = 0.078, the standardized root mean squared residual (SRMR) = 0.080).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents reported the degree to which they used each motive when engaging in their daily activities, using a seven-point Likert scale ranging from 1 (not at all) to 7 (very much). The scale has been found to have good psychometric properties in Chinese samples [ 9 ]. In the present study, the two-factor model had an adequate fit index (χ 2 (29) = 84.52, χ 2 /df = 2.92, the comparative fit index (CFI) = 0.95, the Tucker-Lewis index (TLI) = 0.93, the root mean square error of approximation (RMSEA) = 0.078, the standardized root mean squared residual (SRMR) = 0.080).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, researchers divided the hedonic orientation into the pleasure orientation and the relaxation orientation and found that the pleasure orientation was generally beneficial to individual well-being, whereas the relaxation orientation had a neutral or even detrimental effect [ 7 , 8 ]. However, other studies suggested that the types of hedonic orientation are indistinguishable from one another [ 5 , 9 ]. Culture may also be a factor in determining the way in which pursuing hedonia and eudaimonia affects individual well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese version of the Hedonic and Eudaimonic Motives for Activities-Revised scale (HEMA-R) was used to measure the hedonic and eudaimonic orientations of the respondents when approaching their activities [ 30 ]. Respondents were asked to rate on a 7-point Likert-type scale from 1 (not at all) to 7 (very much) to what degree they typically approach their activities.…”
Section: Methodsmentioning
confidence: 99%
“…Participants indicated the degree to which they used each motive in their daily activities on a seven-point Likert scale ranging from 1 (not at all) to 7 (very much). The scale has been found to have good psychometric properties in Chinese samples ( Li et al, 2021 ). In the present study, Cronbach’s α coefficient was 0.80 for hedonic orientation and 0.81 for eudaimonic orientation.…”
Section: Methodsmentioning
confidence: 99%